Precedent Religious Names in T. Shevchenko’s Ego-texts (Linguostylistic Studies, 2017)
The article explores peculiarities of the precedent religious names functioning in the ego-texts/diaries of T. Shevchenko. The Christian mono-theonyms prevail in the poet’s diary records, that manifests and testifies his deep religiosity, and these names themselves are an integral part of the first circle of his theonymic frame. But T. Shevchenko uses precedent poly-theonymic names of antiquity mainly in a figurative meaning, intellectualizing his records content. The most frequently used precedent Christian agionyms are those which are used with reference to the Mother of God. It has been deduced that none of these agionyms is used with a negative, ironic or humorous connotation at all, as it has been observed in cases with some other precedent religious names. It confirms T. Shevchenko’s extraordinary respect to Virgin Mary.
Keywords: epistolary discourse; diary discourse; precedent religious name; precedent religious phenomenon; Ego-text